A Review of Integrated Courses in Pharmacy Education and Impact of Integration in Pharm D Curricula - Maryam Nikanmehr; Leila Kouti; Kaveh Eslami (Research Center for Rational Use of Drugs (RCRUD), 2017)
Today, due to ever-increasing knowledge and large volumes of information, educational planners of various fields around the world, have been seeking to establish a better and faster refresh for learning. Integration can be a good educational strategy by blending different subjects and contents when presented to students. The aim of this study is to evaluate the medical literature about integration in the curriculum; its process, importance, necessity and different types of it. This review article was prepared by searching the PubMed database, Google Scholar and science direct websites, national and international journals in the field of medical education curricula. The keywords were educational planning, curriculum integration, and medical education with integration and incorporation. Integration and its eleven steps can be an important strategy in educational planning. According to various studies, integration can enhance the students' learning and skills in medicinal and pharmaceutical care. It also improves the satisfaction of faculty and students, the quality of education and increases the students' grades at their examinations. Considering the proper planning, cooperation and co-teaching of faculty members, focus on the desired performance of students and correct assessment of the fundamental principles of integration are crucial to this strategy.